(untitled) (KULT_online, 2025)
Decolonial Archival Futures offers a comprehensive exploration of the development of Indigenous knowledge management within a colonial past, culminating in a critical assessment of the imperative for new ethical management practices for Indigenous records. In the context of the decolonial turn, the text elucidates the multiple possibilities, constraints, and the key role of archival practices for and by Indigenous peoples.